PENGARUH PERSEPSI DUKUNGAN ORGANISASI DAN KETERIKATAN KARYAWAN TERHADAP TURNOVER INTENTION KARYAWAN DI PT SURGANYA MOTOR INDONESIA - Andini, Asri Dwi; Purwadhi , Purwadhi; Andriani, Rian (Universitas Putera Batam, 2024)
Turnover intention is a situation where employees have the intention or desire to leave the company where they work. Perceptions of organizational support and employee engagement are one of the factors that influence high turnover intention. Employees who have perceptions of organizational support and low levels of employee engagement tend to have a higher intention to leave the company. The purpose of this study is to determine and analyze how the description, influence and relationship between perceptions of organizational support and employee engagement affect turnover intention at PT Surganya Motor Indonesia. The population of this study amounted to 640 people. The sampling technique used was purposive sampling with a sample size of 86 people. This type of research is quantitative research with a descriptive approach. The analysis technique used in this research is multiple linear regression analysis technique. The results showed that perceived organizational support and employee engagement had a negative and significant effect on turnover intention. The amount of influence based on the coefficient of determination (R Square) which shows that changes in turnover intention are influenced by perceived organizational support and employee engagement by 47% while the remaining 53% is influenced by other variables or factors such as organizational commitment, organizational culture, leadership style and others. Keywords: Perceived Organizational Support, Employee Attachment, Turnover intention